Polyurethanes modified with functionalized silsesquioxane — synthesis and properties - Pielichowski, K.; Jancia, M.; Hebda, E.; Pagacz, J.; Pielichowski, J.; Marciniec, B.; Franczyk, A. (Polimery, 2013)
Segmental urethane elastomers with built-in chemically reactive nanofiller (propanediolsiloxy-POSS) were prepared by a two-stage (prepolymer) method. The first stage involved bulk-polyaddition reaction of 4,4’-diphenylmethane diisocyanate (MDI, rigid segments) containing the incorporated POSS nanofiller, with poly(oxytetramethylene) glycol (PTMG, soft segments). In the next stage the chain of such prepared isocyanate prepolymer was extended with 1,4-butanediol (BD, soft segment). In this way a series of urethane elastomers containing different amounts (0, 2, 4, 6 wt. %) of POSS moieties was synthesized. The chemical structure of prepared materials was analysed by ATR FT-IR. Using SEM coupled with EDS and mapping capability, the structure of elastomer microdomains and distribution of PDSPOSS molecules in the urethane elastomer was shown. The thermal properties of the materials were characterized using TG and DSC methods. Based on DSC studies, an increase in the glass transition temperature of hard segments with an increase of PDSPOSS content (which may be related to oligosilsesquioxane moieties embedded in this phase) has been found. Thermomechanical properties were tested using DMA and the results show that modification with PDSPOSS gives a possibility to improve the damping properties of polyurethane nanohybrid elastomers. Strength tests have indicated that the addition of PDSPOSS results also in enhanced mechanical properties of polyurethane elastomers.